2021
DOI: 10.1155/2021/9931174
|View full text |Cite
|
Sign up to set email alerts
|

Physical Layer Secrecy Analysis of Multihop Hybrid Satellite‐Terrestrial Relay Networks with Jamming

Abstract: This paper explores the secrecy analysis of a multihop hybrid satellite-terrestrial relay network (HSTRN) with jamming, where one satellite source is aimed at communicating with destination users via multihop decode-and-forward (DF) terrestrial relays, in the existence of an eavesdropper. All the destination users are deployed randomly following a homogeneous Poisson point process (PPP) based on stochastic geometry. Each relay operates not only as a conventional DF relay to forward the received signal but also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 35 publications
(58 reference statements)
0
3
0
Order By: Relevance
“…And the definition of secrecy capacity is the capacity difference of the legitimate link and eavesdropper link. Given no direct link of − S E , the secrecy capacity of − S R and − N R D link can be represented as (17) and (20).…”
Section: Sop Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…And the definition of secrecy capacity is the capacity difference of the legitimate link and eavesdropper link. Given no direct link of − S E , the secrecy capacity of − S R and − N R D link can be represented as (17) and (20).…”
Section: Sop Analysismentioning
confidence: 99%
“…Comparing to traditional encryption method at upper layers, physical layer secrecy has become a popular approach for its advantage of preventing information delivery from eavesdropping [17]. And research on physical layer secrecy in HSTRN has become an attractive concern [18][19][20]. [18] gave a performance comparison of AF and DF HSTRN based on multi-antenna relay, and indicated that the proposed DF HSTRN always had a better secrecy performance than AF HSTRN.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation